(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the author analyzes Japan’s contribution to stability and peace in Afghanistan. The concepts of "peacekeeping" and "human security" in Japan’s foreign policy show its strong commitment to peace and stability and Japan’s potential to become one of the leading countries in the fight against terrorism. The conferences hosted by Japan served as a platform for the international community to provide moral support for dialogue between Afghans, known as the Tokyo Process for a New Afghanistan. This article analyzed the fact that Japan’s policy in Afghanistan is focused on the construction of a civilian state from a military focus. It was also noted that the stability and recovery of Afghanistan cannot be achieved without cooperation in economic development, security measures, and political processes of the neighboring countries that have close relations with Afghanistan.